2016
DOI: 10.21082/jbio.v8n2.2012.p78-88
|View full text |Cite
|
Sign up to set email alerts
|

Kultur Antera untuk Percepatan Perakitan Varietas Padi di Indonesia

Abstract: <p>Rice is a staple<br />food crop in Indonesia, while the need is increasing due to<br />high rice consumption as well as population increase. The<br />problems can be solved through increase of national rice<br />production. Productivity of lowland and upland should be<br />increased intensively and other potential dry area outside<br />Java and Bali Islands should be considered for extending the<br />area of production. Recently, high yielding variety such as&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In this research, DH plants were identified through their phenotypic performance. Compared to DH plants, haploid plants was shorter with smaller and narrower leaves, sterile panicle, no ligule and auricle (Sah and Niroula 2007;Herawati et al 2008;Safitri et al 2010;Dewi and Purwoko 2012). DH 0 obtained from this experiment were 73 lines or approximately 38.8% from the total survivor plants.…”
Section: Dihaploid Plant Productionmentioning
confidence: 69%
See 4 more Smart Citations
“…In this research, DH plants were identified through their phenotypic performance. Compared to DH plants, haploid plants was shorter with smaller and narrower leaves, sterile panicle, no ligule and auricle (Sah and Niroula 2007;Herawati et al 2008;Safitri et al 2010;Dewi and Purwoko 2012). DH 0 obtained from this experiment were 73 lines or approximately 38.8% from the total survivor plants.…”
Section: Dihaploid Plant Productionmentioning
confidence: 69%
“…deletions in plastid DNA, mutations in genes responsible for chlorophyll biogenesis, a metabolic block in pathways leading to chlorophyll biosynthesis, or an impaired photosynthetic apparatus leading to photo-bleaching (Yao and Cohen 2000;Dewi and Purwoko 2008;Dewi and Purwoko 2012;Makowska and Oleszczuk 2014). Albinism reducing efficiency of green plantlets production and may be the cause of low adoption of anther culture technique for rice breeding (Dewi et al 2009;Kumari et al 2009).…”
Section: Plant Regenerationmentioning
confidence: 99%
See 3 more Smart Citations